Análisis Financiero de efectivo y equivalente de efectivo y ratio de liquidez de Agropemin E.U 2018-2019 (2021)
Financial analysis is the tool that allows to determine the financial situation of the company facilitating decision making; The Epsagro are companies that provide direct or rural technical assistance, among them we find AGROPEMIN E.U located in Duitama city, which provides this service in several municipalities in the department of Boyacá. Due to changes in the administration, Agropemin requires a study of its financial situation during the 2018-2019 periods. From the preparation of the cash flow statement and other information provided by the entity, a financial analysis of the cash and cash equivalent account is carried out, as well as the liquidity of the company in order to provide information that allows the taking of decisions by the new administration. It is concluded that the company has financial muscle to meet its short-term